Black-Tailed Prairie Dog (Cynomys ludovicianus) Reintroduction Can Limit Woody Plant Proliferation in Grasslands - Hale, Sarah L.; Koprowski, John L.; Archer, Steven R. (Frontiers in Ecology and Evolution, 2020)
Tree and shrub proliferation has been widespread in grasslands worldwide, and has altered ecosystem function and wildlife habitat. Several causes have been proposed for the woody plant encroachment phenomenon. The widespread eradication of a native keystone herbivore in North American grasslands, the prairie dog (Cynomys spp.), is one potential contributing factor that has received relatively little attention. We hypothesized prairie dogs would have historically suppressed woody plants by creating “browse traps” through their systematic clipping of vegetation. We tested this hypothesis by conducting surveys and experimentally manipulating shrub accessibility via exclosures and artificial saplings on and around recently reestablished black-tailed prairie dog (C. ludovicianus) colonies in southeastern Arizona, USA. Shrubs were common on the nascent colonies (mean ± SE = 132 ± 32.7 plants ha-1), but at substantially reduced densities compared to off colonies (305 ± 94.9 plants ha-1). Among branches placed on colonies to simulate ‘saplings’, 89% were damaged within three days of ‘planting’, whereas those placed off colonies were virtually untouched. This was true for both a deciduous, N2-fixing shrub (velvet mesquite, Prosopis velutina) and an evergreen non-N2-fixing shrub (creosote bush, Larrea tridentata). Prairie dogs on newly established colonies did not extirpate woody plants over the time-frame of our study, but reduced their abundance and suppressed their growth, which would ostensibly prevent them from achieving dominance. Implications for extending the longevity of widely practiced ‘brush management’ grassland restoration treatments are discussed in the context of perceptions of prairie dogs as rangeland pests. Prairie dogs represent an enigma in keystone conservation. Whereas the reintroduction of large or charismatic keystone species (e.g. sea otters [Enhydra lutris]) are conducted to restore critical ecological function, reintroductions of other keystone species, such as gray wolves [Canis lupus] and in our case, prairie dogs, are highly controversial. Our findings suggest reintroductions of this negatively perceived small herbivore could function as a tool to locally suppress woody plant proliferation that is widely regarded as an impediment to livestock production. Accordingly, prairie dogs could promote restoration efforts to re-establish and maintain habitat for grassland endemics while promoting biological diversity and other ecosystem services.